Flammulinavelutipes Polysaccharides Modulate Gut Microbiota and Alleviate Carbon Tetrachloride-Induced Hepatic Oxidative Injury in Mice - Xu, Yingyin; Zhang, Zhiyuan; Wang, Bo; He, Xiaolan; Tang, Jie; Peng, Weihong; Zhou, Jie; Wang, Yong (Frontiers in Microbiology, 2022)
A carbon tetrachloride-induced acute liver injury mouse model is used to study the regulation of gut microbiota and hepatoprotective effect of polysaccharides from Flammulina velutipes (FVPs). The hepatoprotective effect of the FVPs leads to reduced levels of serum aspartate transaminase (AST), alanine aminotransferase (ALT), triglyceride (TG), total cholesterol (TC), total bile acid (TBA) content, and change in liver histopathology. Their anti-oxidant activity is exhibited by decreased levels of hepatic malonaldehyde (MDA) and protein carbonyl (PC) content and increased catalase (CAT) and superoxide dismutase (SOD) content. The anti-inflammatory ability of the FVPs is reflected in a decrease in pro-inflammatory cytokines (including IL-6, IL-1β, and TNF-α). 16S rRNA sequencing shows that the FVPs change the composition of the gut microbiota. A subsequent metabolomics analysis of the gut bacteria (UHPLC–MS/MS-based) revealed that fatty acid biosynthesis, tryptophan metabolism, and metabolism of xenobiotics by cytochrome P450 play important roles in the hepatoprotective effect. This study provides a potential way to modulate gut microbiota and manage liver diseases using natural products.